2004
DOI: 10.1080/09546630410015538
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and follow‐up of persistent granulomatous cheilitis with intralesional steroid and metronidazole

Abstract: Granulomatous cheilitis (GC) is a chronic edema which frequently affects the upper lip due to granulomatous inflammation. Its etiology is currently unknown. This rare disease is generally accompanied by Melkersson-Rosenthal syndrome (MRS), characterized by scrotal tongue, orofacial edema and facial paralysis. However, it is also known to develop only with orofacial edema. Granulomatous cheilitis is a difficult disease to treat because of recurrences. There are contradictory reports about the results of treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…Further attention has been garnered by metronidazole, particularly given the association of GC with Crohn disease noted in much of the literature 13,21,22 . Mixed but promising results have been obtained in the treatment of GC with metronidazole using doses of 750–1000 mg daily 10,21,23 …”
Section: Antibioticsmentioning
confidence: 99%
“…Further attention has been garnered by metronidazole, particularly given the association of GC with Crohn disease noted in much of the literature 13,21,22 . Mixed but promising results have been obtained in the treatment of GC with metronidazole using doses of 750–1000 mg daily 10,21,23 …”
Section: Antibioticsmentioning
confidence: 99%
“…Coskun et al have reported successful results with a combination of intralesional steroids and metronidazole [20]. Similarly, Stein and Mancini treated two children successfully, with a combination of oral prednisolone and minocycline [21].…”
Section: Discussionmentioning
confidence: 99%
“…[13] Similarly, Coskun et al have reported successful results with a combination of intralesional steroids and metronidazole. [14] Combined therapeutic regimen of intralesional triamcinolone, metronidazole and minocycline with weekly intralesional triamcinolone acetonide injections 10 mg/mL in the upper lip (0.25-0.50 mL at three points) for 4 weeks; oral metronidazole tablets 400 mg three times a day and oral minocycline 100 mg daily for one month have yielded excellent response in case studies. A significant decrease in swelling was noticed in these patients after a period of 15 days.…”
Section: Discussionmentioning
confidence: 99%